Extraction of restricted lexical combinations by detecting non-compositionality of multiword expressions - Veloso, Joana Isabel da Silva (2016)
In this article an evaluation of a method for extracting restricted lexical combinations from parallel corpora by detecting non-compositionality of multiword expressions in translation will be presented. This method presupposes that by finding sequences of words whose translation does not follow a simple word-to-word conversion of the component words, a collocation is probably present. Word bigrams are used.